ANALISIS PERTUMBUHAN DAN KETIMPANGAN PENDAPATAN PER KAPITA ANTARKABUPATEN/KOTA DI PROVINSI SUMATERA BARAT TAHUN 1991-2010 - , Tohapmartua Nababan, Dra. CH. Suparmi, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to (1) Analyzing the economic typology kabupayen/city before and after the expansion period of 1991-1999 and 2000-2010 peiod, (2) analyze the inequality of income per capita in the period before and after the devision year 1991-1999 period and the period 2000-2010, (3) to analyze whether the level of labor force participation, developmen aid and investment are realized as well as region expansion effect on the inequalitybof income per capita in the period 1991-2010. The data used is GDP per capita, population data on the number of districts/city and province of West Sumatra in 1991-2010, data rate of labor force participation, the development assistance funds realized and data of foreign and domestic investmen are realized and the dummy division in 1991-2010. The results according to the typology suggest that a shif Klassen typology of region before and after the devision. Three region shifted from quadrant I to quadrant III, and five region shifted from quadrant II into quadrant IV. Inequality of income per capita in the period before and after the expansion period of 1991-1999 and in 2000-2010, based on the Theil index and index trens Williamson to decrease but still relatively high ineuality. Based on the results of the regressio only variabels that labor force participation rate signifikan inequality affects per capita income in the period 1991-2010